A scientometric review of global research on technology in physical education - Daharis; Novri Gazali; Feby Elra Perdima; Khairul Hafezad Abdullah; Ahmad Rahmadani (Journal Sport Area, 2023)
Since COVID-19, technology-based physical education has been normal and is emerging. This paper is intended to identify the development of scientific publications and map educational technology research pertinent to physical education. The keywords "technology" and "physical education" were searched for in the Scopus and Web of Science databases for this study. The number of papers obtained was 1120. The results of mapping this topic reflected fluctuating trends. Between 2020 and 2021, there was a notable rise in this subject resulting from the breakout of the COVID-19 virus and the subsequent protracted pandemic, which compelled most individuals to rely on technology for learning, including physical education. The source that contributed the most to technology and physical education was the "Journal of Physics: Conference Series." With eight articles, Mikhail Kolokoltsev of the Irkutsk National Research Technical University, Russia, contributed the most to technology and physical education. The most influential and widely cited paper was entitled "Final condition screening system of boys aged 15–17 years in the process of physical education" by Olena et al., 2017. The most frequently used keywords were "physical education," "technology," and "college physical education." With 421 articles, China contributed the most to technology and physical education. This study restricted its search to the years 2017-2021. In light of this, it will be crucial for future studies to create a comprehensive map by examining the first year of publications on this subject. It can be used as a guide to look at more interesting pictures that have not been evaluated or looked at yet.